RAISING THE LEVEL OF REGION COMPETITIVENESS BY OPTIMIZATION OF BUDGET POLICY - Nikita A. Moiseev; Sergey V. Manakhov; Olga G. Demenko (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article provides analysis of budget policy of the region administration in the part of its impact on territory competitiveness. The analysis is based on accepted approaches to assessment of the competitiveness level due to their advantages in comparison with other methods. To tackle the set task the authors conducted correlation analysis of interaction between the competitiveness index and the share of expenses on concrete item of the Russian Federation budget. By tracing dynamics of indices correlation the authors proved their continuity in time and in this way they formulated objective recommendations for the region administration aimed at raising the level of competitiveness of the entity through re-distribution of budget expenses.